Factors influencing the customers for not availing illusions from home decor of Berger Paints Bangladesh Ltd. - Musad- Al- Shehab (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.